Analisis Framing Pemberitaan Persentase Kenaikan UMP DKI Jakarta pada Media Online Kompas.com dan CNN Indonesia.com - Fira Pebriyani; Hendra Setiawan (Peneliti.net, 2023)
The increase in the percentage of UMP DKI Jakarta has been hotly discussed by people living in the capital city. There was resistance from various parties regarding the increase figure set by the government. Therefore, the researcher wants to know how the media Kompas.com and CNN Indonesia.com package the news about the increase in the percentage of UMP DKI Jakarta by using Zhongdang Pan and Kosicki's framing analysis theory. This study uses a descriptive qualitative method with data collection techniques, namely reading and paying attention to news related to reporting on the percentage increase in UMP in DKI Jakarta on Kompas.com and CNN Indonesia.com media. This study found that the media analyzed by Kompas.com and CNN Indonesia.com had similarities and differences. The equation can be seen as a script structure which both are equipped with 5W+1H. The two media emphasize maximizing the government's role in making the decision to increase the DKI Jakarta UMP, it's just that Kompas.com media gives how the community or various parties respond to this policy. it's different, with CNN Indonesia which does not provide public opinion regarding policies, and focuses on the origins of calculating the DKI Jakarta UMP determination.